The Hubungan Keberadaan Perokok Dan Bahan Bakar Memasak Dengan Kejadian Infeksi Saluran Pernapasan Akut (ISPA) Pada Balita Di Kecamatan Kelekar, Gelumbang, Dan Lembak - Putri Utami; Prihatini Dini Novitasari; Maurend Yayank Lewinsca; Ayu Novitrie; Fatria Harwanto (Jurnal Riset Kesehatan Nasional, 2025)
Abstract Acute Respiratory Infection (ARI) remains a leading cause of morbidity among children under five in Indonesia. Household environmental factors, such as the presence of smokers and the type of cooking fuel used are often associated with an increased risk of ARI. This study aimed to analyze the association between these factors and ARI incidence among children under five in Kelekar, Gelumbang, and Lembak Subdistricts, Muara Enim Regency. A cross-sectional design was applied with a total sample of 1,276 households with children under five, obtained through total sampling. Data were collected using the 2024 PBL FKM Unsri questionnaire and analyzed with the Chi-Square test. Results showed an ARI prevalence of 5.9%; 75.2% of children lived with smokers, and 97.9% of households used clean fuels (gas/electricity). Bivariate analysis indicated no significant association between the presence of smokers and ARI incidence (p=0.981) nor between the type of cooking fuel and ARI incidence (p=1.000). In conclusion, these two factors were not associated with ARI incidence. Other factors, such as household ventilation, low smoking frequency, outdoor smoking habits, as well as nutritional and environmental conditions, may play a more dominant role in influencing ARI among children under five.   Keywords: toddlers, cooking fuel, the presence of smokers, ARI